Penerapan Program Pembelajaran Vokasional Madrasah Aliyah di MAN 2 Sijunjung - Sri Aisyah Amini; Yuniarti Yuniarti; Asmendri Asmendri; Milya Sari (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2023)
By applying the Madrasah Vocational Education Program, it is expected that student’s creativity will be encouraged in their work, so that after graduating from the Madrasa, their own needs can be met and they become individuals who are independent and not dependent on their parents. The vocational program implemented at MAN 2 Sijunjung relates to the work areas in the community, namely vehicle engineering and clothing design, which are imparted through skills classes. The aim of this study is to determine to what extent the application of professional madrasah learning has developed at MAN 2 Sijunjung. The method used in this research is field research with a qualitative approach. The data collection techniques in this study used documentation and interview techniques. Data analysis techniques were gained from data reduction, presentation and inference to answer the problem formulation and answer the main questions as well as answer the description of the data obtained from the researcher. The conclusion of this study is in the form of a description or description of the implementation of the Madrasah Vocational Learning Program at MAN 2 Sijunjung.